Wage Returns to Human Capital Resulting from an Extra Year of Primary School: Evidence from Egypt - Ragui Assaad; Abdurrahman Aydemir; Meltem Dayioglu-Tayfur; Murat G. Kirdar (Institute of Labor Economics (IZA), 2023)
In this paper, we examine the wage returns to an extra year of primary school using a policy reform in Egypt, which reduced compulsory primary schooling from 6 to 5 years. Since this policy changed the duration of primary school while providing the same diploma, we can estimate the human capital effects holding the sheepskin effects constant. We find that the wage returns to an extra year of primary school for Egyptian men aged 24–44 is a statistically insignificant 2–4 percent. Despite the low returns for the overall population, the returns are much higher for men born in rural areas and men whose fathers have low levels of education—indicating important human capital effects for underprivileged boys. Consistent with this result, we find that the policy effects of a one-year reduction in primary schooling on schooling attainment at various levels are more adverse for underprivileged boys. Our findings, therefore, suggest that such a policy could be particularly detrimental for students from lower socioeconomic groups—contributing to increased inequality.
Keywords: J18; J31; I21; I28; 330; returns to schooling; early human capital investment; instrumental variables; compulsory education duration; Egypt